Schwarze Bürgerrechte und liberaler Antikommunismus: die NAACP in der McCarthy-Ära - Berg, Manfred (Vierteljahrshefte für Zeitgeschichte, 2003)
The impact of the Cold War on the Afro-American civil rights struggle is a hotly contested issue among historians. On the one hand, America's claim to the leadership of the "free world" was incompatible with domestic racial discrimination and provided the civil rights movement with a potent argument. On the other hand, the anti-communist hysteria of the early Cold War forced black leaders to either join the anti-communist bandwagon, or face marginalization and criminalization. In this situation, the National Association for the Advancement of Colored People (NAACP), America's largest and oldest civil rights organization, sided with liberal anti-communism and distanced itself from the left. Recently, historians have argued that the NAACP, by becoming "the left wing of McCarthyism" and purging communists from its ranks, retarded the black struggle for decades. Based on extensive research in the NAACP records, this essay argues that much of this criticism is misleading and inconsistent. By and large, the NAACP remained faithful to its liberal creed, did not implement McCarthy-style "purges", and tried desperately to keep the cause of civil rights on the historical agenda. (Vierteljahrshefte für Zeitgeschichte / FUB)